The Domination Of The Noble Political Elites In Organizing The Government’s Policies In Central Lombok Regency - Abdul LATIF; Arry BAINUS; Yogi Suprayogi SUGANDI; Ari Ganjar HERDIANSAH (Indonesia Strategic Sustainability, 2022)
This study aims to describe the hegemony of the aristocratic political elite in the administration of the government bureaucracy, to reveal the patterns and media of the hegemony of the aristocratic elite in maintaining the status and identity of the power structure, bureaucratic politics and to explain how the political implications of the hegemony of the aristocratic elite on the freedom of local democracy in Central Lombok Regency. The research uses a descriptive qualitative approach, one type of research that is intended to explore and clarify a phenomenon or social reality. By knowing the sources of primary and secondary data, as well as collecting data through in-depth interviews, non-participatory observations and documentation. Analysis of the data using an interactive analysis model. Based on the results of research analysis, the political hegemony of the aristocratic elite is carried out by regional heads as nobles by utilizing the government bureaucratic network through the placement of regional heads. The state civil apparatus from clans, relations and aristocratic relatives in various strategic positions such as heads of offices, and heads of government, patterns and strategies used to carry out political hegemony by the nobility in Central Lombok Regency is to utilize socio-religious organizations such as Nahdlatul Wathan, Islamic Boarding Schools and Islamic Boarding Schools. cultural associations such as the Central Lombok Sasak Cultural and Customary Council which have a wide network spread across the island. In fact, the political hegemony of the aristocratic elite in Central Lombok Regency has negative implications for local democracy.